Combined with UPLC-Triple-TOF/MS-based plasma lipidomics and molecular pharmacology reveals the mechanisms of schisandrin against Alzheimer's disease - Tian-tian Zhao; Ying Zhang; Cheng-qin Zhang; Ya-fei Chang; Mei-rong Cui; Yue Sun; Wen-qian Hao; Yu-meng Yan; Shuo Gu; Yao Xie; Bin-bin Wei (BMC, 2023)
Abstract Background Alzheimer's disease (AD), a type of neurodegeneration disease, is characterized by Aβ deposition and tangles of nerve fibers. Schisandrin is one of the main components of Fructus Schisandrae Chinensis. Researches showed that schisandrin can improve the cognitive impairment and memory of AD mice, but the specific mechanism has not been fully elucidated. Purpose The purpose of this study is to investigate the possible mechanism of schisandrin in improving AD pathology. Methods The Morris water maze test was executed to detect spatial learning and memory. Ultra performance liquid chromatography-Triple time of flight mass spectrometry (UPLC-Triple-TOF/MS)-based plasma lipidomics was used to study the changes of plasma lipids. Moreover, we measured the levels of protein and mRNA expression of APOE and ABCA1 in the rat brains and in BV2 microglia. Results Our study found that schisandrin could improve learning and memory, and reduce Aβ deposition in AD rats. Furthermore, we found that schisandrin can improve plasma lipid metabolism disorders. Therefore, we hypothesized schisandrin might act via LXR and the docking results showed that schisandrin interacts with LXRβ. Further, we found schisandrin increased the protein and mRNA expression of LXR target genes APOE and ABCA1 in the brain of AD rats and in BV2 microglia. Conclusion Our study reveals the neuroprotective effect and mechanism of schisandrin improves AD pathology by activating LXR to produce APOE and ABCA1.